2021
DOI: 10.1111/anu.13260
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alternate‐day feeding on growth and feed conversion in Atlantic cod Gadus morhua

Abstract: This study aimed to investigate the effect of alternating feeding (Alt) compared with control being fed every day (Con) in the on‐growth face of Atlantic cod. Individually marked fish (198 and 98 in the Con and Alt groups, respectively) was sampled for weight and length on 6 occasions over a 15‐month period, where mean weight increased from 628 and 758 g to 2635 and 3041 g, for the Con and Alt groups, respectively. Feeding alternate day resulted in 13 percentage more weight gain in the alternating feeding grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…During the rearing trial, eels fed on alternate days for 78 d consumed 0.54 kg of feed compared to almost 2 kg for those fed daily for 155 d. The reduction in total feed consumption in the ADF group while attaining a similar weight gain further supports the observed compensatory growth in this species. Improved feed use efficiency may be due to reduced feed waste through consumption of lower amounts of feed (Hezron et al 2019;Bjørnevik et al 2021). On the other hand, the poor growth, increased competition for feed, and mortalities could result from intermittent feeding (Abel-Hakim et al 2006) which were not observed in this study, particularly in the ADF group.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…During the rearing trial, eels fed on alternate days for 78 d consumed 0.54 kg of feed compared to almost 2 kg for those fed daily for 155 d. The reduction in total feed consumption in the ADF group while attaining a similar weight gain further supports the observed compensatory growth in this species. Improved feed use efficiency may be due to reduced feed waste through consumption of lower amounts of feed (Hezron et al 2019;Bjørnevik et al 2021). On the other hand, the poor growth, increased competition for feed, and mortalities could result from intermittent feeding (Abel-Hakim et al 2006) which were not observed in this study, particularly in the ADF group.…”
Section: Resultsmentioning
confidence: 63%
“…Feeding management strategies such as skip or alternate day feeding have been studied in a number of species such as Nile tilapia Oreochromis niloticus (Bolivar et al 2006;Cuvin-Aralar et al 2012), milkfish Chanos chanos (de Jesus-Ayson and Borski 2010), and in Atlantic cod Gadus morhua (Bjørnevik et al 2021). Such studies found that this feeding schedule resulted in comparable fish performance and lower feed conversion ratio compared to those fed daily.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of our observations, Bolivar et al [ 24 ] found that fish fed daily had higher growth but did not significantly differ with those fed alternate-day feeding (EOD), they reported that a significantly better FCR was obtained for fish fed EOD or on alternate days than for fish fed daily. In the same trend [ 25 ], found that, alternate-day feeding (EOD) group consumed significantly less feeding (27 %) compared with group that fed every day, while [ 26 ] pronounced that fish fed alternate-days solely had half of the days of feeding in contrast fish fed constantly and then FCR was once the exceptional with alternate-day feeding (EOD). Similar observations have been mentioned by Ref.…”
Section: Discussionmentioning
confidence: 84%
“…It is well known that growth performance is an essential criteria for evaluating fishmeal alternatives. Even though a great deal of research has been conducted on alternate feeding strategy in fish (10,11,19), the impacts of new proteins on the growth performance of fish under alternate feeding strategy have not been investigated. In the present research, a substantial decrease in growth performance was detected when comparing diets containing novel proteins to whole fish meal diet; nevertheless, the most surprising discovery was that the growth rate in the second 29 days outperformed the first 29 days.…”
Section: Growth Performance Feed Utilization and Intestinal Histologi...mentioning
confidence: 99%
“…Alternate feeding strategy is an effective method to conserve high-value or resource-limited feed ingredients. Some studies have extensively conducted for fish oil based diet substitution with terrestrially derived oil or plant-sourced oil diets without compromising fish fatty acid composition (10), fish growth performance (11), or their physio-biochemical performance (12,13) in Scophthalmus maximus, Gadus morhua, Dicentrarchus labrax, and Acanthopagrus schlegelii. These studies showed that using an alternate feeding strategy could reduce the use of fish oil.…”
Section: Introductionmentioning
confidence: 99%